Extracting geometric models from medieval moundling profiles for case-based reasoning - BRADSHAW, GARETH; O'SULLIVAN, CAROL ANN (My University, 2000)
Cross-sectional profiles of medieval mouldings are often considered to be a vital form of data for art historians. Mouldings have often been used to highlight salient areas of buildings, and they provide a wealth of information. To date, little use of computer technology has been made in their acquisition, storage and analysis. The paper presents a representation for such planar curves, and an algorithm for its extraction from planar curves. The representation uses geometric primitives, specifically line and ore segments, which allow the curves to be represented in a compact form, approximating the circular sections more effectively than using linear segments alone. These idealised models provide templates which provide a means for the identification of specific features, within profiles, which can then serve as characteristics for use in case-based reasoning.
PUBLISHED
Keywords: architecture; case-based reasoning